CULTURE SHOCK SEBAGAI PROSES NEGOSIASI MAKNA: STUDI INTERPRETATIF MAHASISWA PERANTAU DI YOGYAKARTA - Ikhtiara, Seiren (SOURCE : Jurnal Ilmu Komunikasi, 2026)
Culture shock is a common experience in intercultural communication contexts, yet it is often narrowly understood as an individual adaptation problem or psychological stress. This article aims to examine culture shock as a process of meaning negotiation in communication adaptation, positioning anxiety and uncertainty as dynamic elements of social interaction. The study employs a qualitative interpretative approach using thematic analysis of in-depth interview data collected from ten informants. The analysis focuses on how intercultural communication experiences are interpreted and negotiated in everyday interactions. The findings reveal four main themes: an initial phase of alienation and meaning confusion, self-reflection on cultural differences, negotiation of meaning in social interactions, and communicative adaptation marked by increased comfort and contextual understanding. The results indicate that effective communication adaptation is not characterized by the elimination of anxiety and uncertainty, but by the ability to manage and interpret them reflexively. Using the framework of Anxiety/Uncertainty Management (AUM) Theory, this article argues that culture shock constitutes an integral part of an ongoing intercultural communication adaptation process. This study contributes to strengthening the interpretative perspective in intercultural communication research.